THE EFFECT OF CARBON COATING ON STAINLESS STEEL 316L WITH VARIATIONS OF HARDENING PROCESSES (PACK CARBURIZING AND QUENCING) AND TEMPERATURE ON CONDUCTIVITY AND CORROSION RATE - cristian bala mudha; Nereus Tugur Redationo; Bernardus Crisanto Putra Mbulu (Universitas Katolik Widya Karya Malang, 2025)
Stainless steel is an alloy steel with corrosion (rust) resistance properties. However, the good corrosion and wear resistance properties of stainless steel also require continuous improvement in its performance and service life, especially in highly aggressive environments. One approach to changing the material structure is by using a mixture based on natural carbon, such as robusta coffee grounds. Robusta coffee grounds will be converted into carbon using a pyrolysis process at a temperature of 1000°C with a holding time of 1 hour. This carbon will be used as a coating material on 316L stainless steel with a variety of pack carburizing and quenching processes and temperatures with a holding time of 1 hour, then it will undergo a testing process that includes: thermal conductivity testing, and corrosion rate testing. In the quenching process, the thermal conductivity value of 900°C has a thermal conductivity value of 20.556 W/m°C, 800°C has a thermal conductivity value of 19.669 W/m°C and a temperature of 700°C with a thermal conductivity value of 18.930 W/m°C. while in the pack carburizing process, the temperature of 900°C has a thermal conductivity value of 20.101 W/m°C, and 800° has a thermal conductivity value of 19.54684 W/m°C, while at 700°C the thermal conductivity value is 18.916 W/m°C. At the raw corrosion rate has a corrosion rate value of 7.614 mm/year, in the quenching process of 700°C has a corrosion rate of 12.781 mm/year, while the temperature of 900°C with a corrosion rate value of 18.401 mm/year, and in the pack carburizing process of 700°C has a corrosion rate value of 9.699 mm/year temperature 900°C with a corrosion rate value of 13.234 mm/year. The better process in thermal conductivity is quenching, because it has a faster time but has a high conductivity value, while for the best corrosion rate is the pack carburizing process because it has a smaller corrosion rate value compared to the quenching process